NADPH oxidases as drug targets and biomarkers in neurodegenerative diseases: What is the evidence? - Sorce, S.; Stocker, R.; Seredenina, T.; Holmdahl, R.; Aguzzi, A.; Chio, A.; Depaulis, A.; Heitz, F.; Olofsson, P.; Olsson, T.; Duveau, V.; Sanoudou, D.; et al. (Free Radic Biol MedFree Radic Biol MedFree Radic Biol Med, 2017)
Neurodegenerative disease are frequently characterized by microglia activation and/or leukocyte infiltration in the parenchyma of the central nervous system and at the molecular level by increased oxidative modifications of proteins, lipids and nucleic acids. NADPH oxidases (NOX) emerged as a novel promising class of pharmacological targets for the treatment of neurodegeneration due to their role in oxidant generation and presumably in regulating microglia activation. The unique function of NOX is the generation of superoxide anion (O2(*-)) and hydrogen peroxide (H2O2). However in the context of neuroinflammation, they present paradoxical features since O2(*-)/H2O2 generated by NOX and/or secondary reactive oxygen species (ROS) derived from O2(*-)/H2O2 can either lead to neuronal oxidative damage or resolution of inflammation. The role of NOX enzymes has been investigated in many models of neurodegenerative diseases by using either genetic or pharmacological approaches. In the present review we provide a critical assessment of recent findings related to the role of NOX in the CNS as well as how the field has advanced over the last 5 years. In particular, we focus on the data derived from the work of a consortium (Neurinox) funded by the European Commission's Programme 7 (FP7). We discuss the evidence gathered from animal models and human samples linking NOX expression/activity with neuroinflammation in neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS) and Creutzfeldt-Jakob disease as well as autoimmune demyelinating diseases like multiple sclerosis (MS) and chronic inflammatory demyelinating polyneuropathy (CIDP). We address the possibility to use measurement of the activity of the NOX2 isoform in blood samples as biomarker of disease severity and treatment efficacy in neurodegenerative disease. Finally we clarify key controversial aspects in the field of NOX, such as NOX cellular expression in the brain, measurement of NOX activity, impact of genetic deletion of NOX in animal models of neurodegeneration and specificity of NOX inhibitors.
Sorce, SilviaStocker, RolandSeredenina, TamaraHolmdahl, RikardAguzzi, AdrianoChio, AdrianoDepaulis, AntoineHeitz, FreddyOlofsson, PeterOlsson, TomasDuveau, VenceslasSanoudou, DespinaSkosgater, SaraVlahou, AntoniaWasquel, DominiqueKrause, Karl-HeinzJaquet, VincentengReviewResearch Support, Non-U.S. Gov't2017/08/16 06:00Free Radic Biol Med. 2017 Nov;112:387-396. doi: 10.1016/j.freeradbiomed.2017.08.006. Epub 2017 Aug 12.
Keywords: Amyotrophic Lateral Sclerosis/diagnosis/drug therapy/*enzymology/pathology; Animals; Antioxidants/therapeutic use; Biomarkers/blood; Central Nervous System/drug effects/enzymology/pathology; Creutzfeldt-Jakob Syndrome/diagnosis/drug therapy/*enzymology/pathology; Disease Models, Animal; Europe; gene expression; Humans; Hydrogen Peroxide/metabolism; International Cooperation; Microglia/drug effects/enzymology/pathology; Multiple Sclerosis/diagnosis/drug therapy/*enzymology/pathology; NADPH Oxidase 2/antagonists & inhibitors/blood/*genetics; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating/diagnosis/drug; Superoxides/metabolism; therapy/*enzymology/pathology